2020
DOI: 10.1002/jlb.3ri1219-425r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IgE by T follicular helper cells

Abstract: Allergies to food and environmental antigens have steeply grown to epidemic proportions. IgE antibodies are key mediators of allergic disease, including life‐threatening anaphylaxis. There is now compelling evidence that one of the hallmarks of anaphylaxis‐inducing IgE molecules is their high affinity for allergen, and the cellular pathway to high‐affinity IgE is typically through sequential switching of IgG B cells. Further, in contrast to the previously held paradigm that a subset of CD4+ T cells called Th2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 119 publications
(315 reference statements)
0
29
0
Order By: Relevance
“…High‐affinity IgE is more pathogenic at inducing allergic responses than low‐affinity IgE 88 . Nevertheless, how T FH cells instruct high‐affinity IgE production remains largely unknown.…”
Section: Tfh and Tfr Cells And Ige Affinitymentioning
confidence: 99%
“…High‐affinity IgE is more pathogenic at inducing allergic responses than low‐affinity IgE 88 . Nevertheless, how T FH cells instruct high‐affinity IgE production remains largely unknown.…”
Section: Tfh and Tfr Cells And Ige Affinitymentioning
confidence: 99%
“…High-affinity, but not low-affinity IgE is known to cause anaphylaxis. 5 A recent study found that OVM-sIgE avidity was more effective at differentiating clinically reactive egg-allergic patients from those tolerant of heated egg compared to EW-sIgE. 4 We found that the ratio of OVM-sIgE to OVM-sIgD or sIgG4 in the CAE group was significantly higher compared to the PAE, OGE, and NEA groups (Figure 2).…”
Section: Ovomucoid-specific Igd Increases In Children Who Naturally Outgrow Egg Allergy In a Cross-sectional Studymentioning
confidence: 66%
“…However, it was reported that a distinct T FH population, named T FH 13, can produce both IL‐4 and IL‐13, and is induced in response to allergens but not helminths [65]. T FH 13 was required for the production of high‐affinity IgE capable of inducing anaphylactic responses in mouse models, and was also identified in the same study in the blood of patients with food allergies [65, 66] (Fig. 1).…”
Section: Ige Production and Ige Repertoires In Food Allergymentioning
confidence: 93%